Conditionally Activated E7 Proteins of High-Risk and Low-Risk Human Papillomaviruses Induce S Phase in Postmitotic, Differentiated Human Keratinocytes - Banerjee, N. Sanjib (American Society for Microbiology, 2006)
The productive program of human papillomaviruses (HPVs) in epithelia is tightly linked to squamous differentiation. The E7 proteins of high-risk HPV genotypes efficiently inactivate the pRB family of proteins that control the cell cycle, triggering S phase in suprabasal keratinocytes. This ability has until now not been demonstrated for the low-risk HPV-6 or HPV-11 E7 proteins. An inducible system in which HPV-16 E7 is fused to the ligand binding domain of the human estrogen receptor (ER) was described by Smith-McCune et al. (K. Smith-McCune, D. Kalman, C. Robbins, S. Shivakumar, L. Yuschenkoff, and J. M. Bishop, Proc. Natl. Acad. Sci. USA 96:6999-7004, 1999). In the absence of hormone, E7ER is cytoplasmic, and upon addition of 17β-estradiol, it translocates to the nucleus. Using organotypic epithelial raft cultures developed from primary human keratinocytes, we show that 16E7ER promotes either S-phase reentry or p21cip1 accumulation in differentiated keratinocytes in a stochastic manner as early as 6 h postinduction with 17β-estradiol. A vector expressing the ER moiety alone had no effect. These observations prove unequivocally that the E7 protein drives S-phase reentry in postmitotic, differentiated keratinocytes rather than preventing S-phase exit while the cells ascend through the epithelium. HPV-11 E7ER and, much less efficiently, HPV-6 E7ER also promoted S-phase reentry by differentiated cells upon exposure to 17β-estradiol. S-phase induction required the consensus pRB binding motif. We propose that the elevated nuclear levels of the low-risk HPV E7 protein afforded by the inducible system account for the positive results. These observations are entirely consistent with the fact that low-risk HPV genotypes replicate in the differentiated strata in patient specimens, as do the high-risk HPVs.